Multi-Segmental Evaluation of Intestinal Permeability of Amlodipine at Two Dose Levels - Ateş, Müge; Stelmasińska, Agata Bogacz; Stelmasińska, Michał; Barre, Liban; Büyüktuncel, Ebru; Kaynak, Mustafa Sinan; Şahin, Selma (Current Pharmaceutical Design, 2025)
<span class=
Keywords: Perfusion coefficient